KEPADATAN POPULASI KEPINDING TANAH (Scotinophara coarctata) DI AREAL PERSAWAHAN - HAVIZ, M.; Nurhadi, Nurhadi; Srisasmita, Ayu (Sainstek : Jurnal Sains dan Teknologi, 2011)
The objective of this research is to find out the density of bedbug population in Jorong Mahakarya Kenagarian Koto Baru, sub-district Luhak Nan Duo, Pasaman Barat regency. This research was conducted through a descriptive survey and direct collection of the Scotinophara coarcrata in the area of paddy field by using sticky trap. In order to collect the object, it was ordinal sampling used. Sample collecting was done twice at an interval of the first and the second 20 days. As the result of the first collection, it was gained 617 bedbugs with an average 21.27, and of the second collection was obtained 595 bedbugs with an average 20.52. The number of bedbugs collected in both periods was relatively the same. In this case the Scotinuphara coarctatapopulation has exceeded the limit as pests. Based on the research finding, it can be concluded that the density of bedbug population in paddy fields in Kampung Lima, Jorong Mahakarya kenagarian Koto Baru, sub-district Luhak Nan Duo, Pasaman Barat regency has exceeded the limit as pests.Key words: density, population, Scotinophara coarctata